Effect of perceived risk of covid 19 on protective behavioral changes among adult population in pakistan: A web-based cross-sectional study - Barkat, Rahil; Rahim, Anum; Jiwani, Ahsun; Khan, Sherwali; Ali, Saleema (Archives of Community Medicine and Public Health, 2021)
The COVID-19 pandemic is still a global public health issue. Little is known about the treatment, therefore prevention plays a vital role to guard the high risk group. Thus understanding the effect of perceived risk on protective behaviors among our population is essential. The study aims to assess the effect of perceived risk of COVID 19 on protective behavioral changes among adult population in Pakistan. A web based survey was administered to Pakistani adults. Convenience sampling was adopted to assess the knowledge, protective methods and perceived risk towards COVID-19 among the population. Descriptive Analysis along with stepwise multivariable linear regression analysis was performed. There were total of 185 respondents with valid responses. Risk perception mean score was 12.11 (SD=3.97) and the highest mean score was for risk of getting infection and risk of transmitting illness to loved ones that is 3.38 (±1.28) and 3.24 (±1.40) respectively. Avoiding people who are sick had the highest mean score of 4.25 (±1.02) among all protective practices. The linear regression analysis suggests that increase in one unit of risk perception is associated with increase in 0.39 units in overall protective behavior towards covid-19 after adjusting with other independent variables. Similarly, with an increase in 1 unit of knowledge is found to be associated with an increase of 0.045 units of in overall protective behavior (regression coefficient: 0.38, 95% 0.008-0.77) after adjusting with risk perception, gender and educational status. In the end, the study found that the risk perception along with gender, educational background and knowledge has significant impact on preventive behavior towards Covid-19.